Penyelesaian Sengketa Jaminan Fidusia Dalam Praktik Gadai - Arifatul Uyun; Abdul Mujib (Fakultas Hukum, Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2022)
One form of prudence from financial institutions is to ask for a fiduciary assurance from debtors to guarantee debt repayment or fulfillment of the contract in accordance with the agreement. In a fiduciary assurance, the goods that become the fiduciary object cannot be transferred to a third party either by being sold, pawned, and so on without the written permission of the debtor. Debtors who transfer the object of fiduciary security with pledges and defaults, then there are efforts made to resolve them. This research is qualitative research using the descriptive-analytical method. The approach used in this study is a normative juridical approach, by examining the settlement of disputes in fiduciary assurance which are transferred with a pledge by the debtor. The results of this study indicate that a fiduciary assurance is an additional agreement that previously contained a main agreement by the parties, while the object of a fiduciary assurance is movable and immovable goods, tangible or intangible, except for mortgages, ship mortgages, mortgages airplanes, and pawns. Efforts to resolve disputes that occur in fiduciary assurance can be carried out by direct approaches, subpoenas, mediation, and execution of the fiduciary object. Disputes that occur in fiduciary assurance, are resolved first in accordance with the material rights attached to the fiduciary object, namely Droit de Preferenc and Droit de Suite rights.